C‐F bond activation by saturated NHC: mesoionic compound formation and its unprecedented adduct with B(C6F5)3 - Pait, M.; Kundu, G.; Tothadi, S.; Karak, S.; Jain, S.; Vanka, K.; Sen, S. S. (Angewandte Chemie - International Edition, 2019)
The reaction of SIPr, [1,3‐bis(2,6‐diisopropylphenyl)‐imidazolin‐2‐ylidene] (1), with C6F6 led to the formation of an unprecedented mesoionic compound (2). The formation of 2 is made accessible by deprotonation of the SIPr backbone with simultaneous elimination of HF. The C−F bond para to the imidazolium ring in 2 is only of 1.258(4) Å, which is the one of the shortest structurally authenticated C−F bonds known to date. The liberation of HF during the reaction is unequivocally proved by the addition of one more equivalent of SIPr, which leads to the imidazolium salt with the HF2− anion. To functionalize 2, the latter reacted with B(C6F5)3 to give an unusual donor–acceptor compound, where the fluoride atom from the C6F5 moiety coordinates to B(C6F5)3 and the carbanion moiety remains unaffected. Such coordination susceptibility of the fluoride atom of a nonmetallic system to a main‐group Lewis acid (Fnon‐metal→BR3) is quite unprecedented.
Keywords: C-F activation; carbanions; N-heterocyclic carbenes; structure elucidation; Ylides